Breeding performance of Common Terns (Sterna hirundo) does not decline among older age classes. (16th May 2020) - Nisbet, Ian C T; Iles, David; Kaneb, Andrew; Mostello, Carolyn S; Jenouvrier, Stéphanie
Abstract: Declines in reproductive performance among older age classes have been reported in many bird and mammal species, and are commonly presented as demonstrating reproductive senescence. However, no declines in performance could be demonstrated in studies of several bird species. We measured reproductive performance in Common Terns ( Sterna hirundo ) of known age (2–28 yr) during a 19-yr period at a site in Buzzards Bay, Massachusetts, USA. We measured 6 components of reproductive performance and used generalized additive mixed models (GAMMs) in a Bayesian framework to analyze dependence of each measure on parental age, while controlling for variations among years and indices of individual quality. Four measures of performance improved (earlier laying date, higher values of clutch size, fledging success, and productivity) with age, most rapidly between ages 2 and 10 yr; egg mass and hatching success varied only slightly with age. No measure of performance showed reversals among the older age classes; fledging success and productivity continued to increase through at least age 22 yr. These findings are consistent with results from an earlier study of the same species. Continued increase in reproductive performance through the oldest age classes is not incompatible with "reproductive senescence" (decline in physiological or other functions required for successful reproduction) if either reproductive effort or efficiency continue to increase. Studies within our population have yielded no evidence for age-related increase in reproductive effort, but 3 studies have suggested that older Common Terns can raise chicks more successfully than younger birds without increasing reproductive effort, probably by more efficient foraging and chick provisioning. Our findings suggest that Common Terns offset reproductive senescence by continuing to improve efficiency through at least age 22 yr. Age-related changes in efficiency should be investigated in other species with similar life-history traits. Abstract : We studied Common Terns (Sterna hirundo) at a breeding colony in Massachusetts from 1970 until 2003: we banded chicks when they hatched so that we could determine their age when they returned to breed at the same site in subsequent years. The terns' breeding success continued to improve with age throughout their lives and was still increasing among birds that were 22 years old. Common Terns continually improve their skills at finding fish and provisioning their chicks, even after 20 years of practice. Graphical Abstract: